2016
DOI: 10.1139/gen-2015-0207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chromosomal localization of 45S and 5S rDNAs and implications for genome evolution inCucumis

Abstract: Ribosomal DNAs are useful cytogenetic markers for chromosome analysis. Studies investigating site numbers and distributions of rDNAs have provided important information for elucidating genome organization and chromosomal relationships of many species by fluorescence in situ hybridization. But relevant studies are scarce for species of the genus Cucumis, especially in wild species. In the present study, FISH was conducted to investigate the organization of 45S and 5S rDNA among 20 Cucumis accessions, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
2
26
1
Order By: Relevance
“…This is underpinned by higher rates of unreduced pollen compared with unreduced eggs in many plant species (Ramsey & Schemske, ). It is conceivable that the remaining chromosomes 1.3 and 2.3 are present in the highly heterozygous C. cartwrightianus gene pool. We propose four losses of 18S‐5.8S‐25S rRNA gene arrays from C. cartwrightianus accessions similar or identical to Evia plant 2, Evia plant 5 and Attica 4 ZN 519, which resulted in saffron chromosomes 5.2, 6.3, 7.1 and 7.2. Chromosomal variability of rDNA sites has been frequently described in plants (Schmidt et al ., ; Zhang et al ., ; Garcia et al ., ). Most importantly, so‐called jumping nucleolus organizing regions have been reported in Allium cepa , like saffron a member of the Asparagales order (Schubert & Wobus, ).…”
Section: Discussionmentioning
confidence: 98%
“…This is underpinned by higher rates of unreduced pollen compared with unreduced eggs in many plant species (Ramsey & Schemske, ). It is conceivable that the remaining chromosomes 1.3 and 2.3 are present in the highly heterozygous C. cartwrightianus gene pool. We propose four losses of 18S‐5.8S‐25S rRNA gene arrays from C. cartwrightianus accessions similar or identical to Evia plant 2, Evia plant 5 and Attica 4 ZN 519, which resulted in saffron chromosomes 5.2, 6.3, 7.1 and 7.2. Chromosomal variability of rDNA sites has been frequently described in plants (Schmidt et al ., ; Zhang et al ., ; Garcia et al ., ). Most importantly, so‐called jumping nucleolus organizing regions have been reported in Allium cepa , like saffron a member of the Asparagales order (Schubert & Wobus, ).…”
Section: Discussionmentioning
confidence: 98%
“…FISH can not only identify the position of a target sequence but also perform its qualitative and relative quantitative analysis by combining labeled nucleic acid probes with chromosomes, interphase nucleus, or DNA fibers. It has been widely used for identifying specific chromosome regions, analyzing their composition, spatial location, and dynamic chromatin changes during the cell cycle [13][14][15]. Additionally, it has been widely used in unraveling the physical map, structure, and evolution of the genome and in analyzing the relationship between species [16][17][18][19][20][21].…”
Section: Of 12mentioning
confidence: 99%
“…Prometaphase chromosomes in Brassica [ 5 ] and rice [ 7 ] have been successfully induced using ethanol and acetic acid (3:1) without pretreatment. Other methods to accumulate metaphase and prometaphase chromosomes, such as with ice water (ice) treatment for 24 h [ 11 ] or 0.002 M 8-hydroxyquinoline (8-Hq) [ 12 , 13 ] have also been reported. Although FISH studies have also been reported in melon [ 12 15 ], most of them used metaphase chromosomes, which are shorter and more compact than prometaphase chromosomes.…”
Section: Introductionmentioning
confidence: 99%